Kajian Yuridis Pengisian Jabatan di Lingkungan Pemerintah Daerah Bondowoso Berdasarkan PERMENPAN RB RI No. 15 Tahun 2019 Tentang Pengisian Jabatan Pimpinan Tinggi Secara Terbuka dan Kompetitif di Lingkungan Instansi Pemerintah - TioAqzha, Raymirzhad; Fauziyah (Indonesian Journal of Law and Justice, 2023)
The public has an important role in choosing regional leaders. Open selection is carried out in order to select officials who have the capacity, competence and integrity to occupy positions in an agency. Pancasila plays an important role as the foundation of the Indonesian state. Implementation of Primary High Leadership Position Selection is one of the activities carried out to find competent and professional leaders. This research is a normative juridical study that analyzes PERMENPAN RB RI No. 15 of 2019 concerning Filling Primary High Leadership Positions as used as a guideline in implementing selection for filling JPT Regional Secretary in Bondowoso Regency; as well as Law no. 5 of 2014 concerning State Civil Apparatus. Based on the results of the existing discussion, the results of this research: first, ASN regulations regarding filling positions which are the main issue in legal incidents have a predetermined format so that they need a more detailed interpretation to help provide solutions related to the same problems within the Indonesian Government. Second, the presence of Law Number 5 of 2014 concerning State Civil Apparatus has indeed used the principle of a merit system so that it can suppress the practice of unscrupulous individuals in the implementation of filling out the Regional Secretary's JPT. As regulated in PERMENPAN RB RI No. 15 of 2019 concerning Filling of Primary High Leadership Positions carried out openly and competitively, missed supervision actually resulted in the filling of the JPT for District Regional Secretary. Bondowoso is impressed that the closer carrier system is not open bidding. The cases that occurred were carried out by unscrupulous individuals, money politics with abuse of position or power created sub-optimality in the implementation of job selection. The effort offered by researchers is to revitalize public participation in the implementation of filling the position of High Leadership Regional Secretary to prevent derivation in the selection of JPT Regional Secretary.